OTONOMI DAERAH DAN PEMBIAYAAN SERTA PENGARUHNYA PADA KINERJA PENDIDIKAN ISLAM - Panggabean, Hadi Saputra (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2019)
Regional Autonomy in the reform era along with changes in legislation regarding the management of the education financing system has had a serious impact on the education system that was initially centralizedto decentralized. This change has a positive impact on the region in the management of education, especially financing in the process of advancing education in each region, especially Islamic education. Because the needs of each region differ in conditions and problems, the central government provides a mandatory through the basic law in Law No. 22 of 1999 concerning regional government and Law No. 25 of 1999 concerning financial balance between the central government and the regions, which was later revised to Law No. 32 of 2004 concerning regional government and Law No. 33 of 2004, namely the regulation of two new regional revenue sources, namely regional balance funds and loans. With the decentralization of central authority to the regions means that a region is given the opportunity to recognize and find solutions to the problems of the region in advancing Islamic education.